(3GdQMdI GdMLGRjI (B1930 (3e(B.-1348 (3g` (B/s - (3GdSdGhj Hh TYQI , eMeO MLj GdgGTejs (3Jhaj (B1951s; (3CHh GdYjO, chKQs ((3GdEeGQGJ GdYQHjI GdeJMOI (B-(3CHh XHj (B:s (3OGQ GdShjOj ,s (3dHfGf (B- (3HjQhJ (B:s (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ,s (3GdCQOf (B- (3YqeGf (B:s (3OGQ GdaGQS ,s, 2023)
(3JbOe gPg GdQMdI GdMLGRjI edeMG WQjaG Yf TNUjI GdeKba GdeZQHj hfXQJg Edi GdBNQ, NGUI aj GdJYQV dbVGjG TGFcI cbVjI GdMLQ GdUMj, hXGgQI GdHOY aj GdeZQH hGdeTQb GdYQHjjf, hZjQgG ef GdbVGjG hGdeSGFd, aVdG Yf JUhQ GdMGL HhTYQI ddMOGKI hGdQMdI LGAJ aj XQa JGQjNj Objb ddZGjI, dSHHjf ChdgeG jJeKd aj GdJMhd GdYGe GdPj WQC Ydi WQjb GdQMdI GdMLjI, hKGfjgeG jJYdb HGdXQha GdJGQjNjI hGdSjGSjI GdJj YQagG GdeZQH hGdeTQb GdeSJYeQjf BfPGc(B. (3hdG Tc Cf gPg GdCLhGA SJLO dgG UOi eHGTQG aj fUhU GdQMdGJ(B. (3GdeMbbI GdJj fGdJ Yf JMbjbgG hOQGSJgG LGFRI GHf HWhWI dCOH GdQMdI JfHg Edi Cf eTGgOGJ GdMGL HhTYQI hedGMXGJg aj GdeTQb de JbJUQ abW Ydi GdeBKQ hGdeRGQGJ GdOjfjI, Hd JYOJgG Edi GdLhGfH GdGLJeGYjI cGfJbGOg dJUQaGJ GdMLGL OGNd GdMQe Gdecj hGSJjGFg CMjGfG aj HYV GdCehQ, Ohf Cf JZad JPqeQg ef HYV GdCSGWjQ hGdNQGaGJ GdeQJHWI HRjGQI GdeBKQ GdeTQbjI(B. (3hbO MGhdJ GdeMbbI GdELGHI HTcd ZjQ eHGTQ Yf CSFdI ETcGdjI MGQbI ef bHjd(B: (3gd GdQMdI eUOQ JGQjNj ? hEPG cGf GdCeQ cPdc, aHCj eYfi ? hgd JSeM WHjYI GdQMdI HGSJcTGa GdbjeI GdeUOQjI dLfS jLeY Hjf GdCOH hGdLZQGajG hGdYLGFH hGdcQGeGJ hTJi CfhGY GdYdhe hGdeYGQa hGdCLfGS(B.s
(3NWhW GdZdGa (B: (3eMeO fLjH HQHhQ ; JUeje GdZdGa (B: (3fGUQ HNjJ ; GdUa GdVhFj (B: (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ(B.s
(3GdcJGH GdMGFR Ydi LGFRI GHf HWhWI aQY JMbjb GdeNWhWGJ (B2020 -2023s
Keywords: (3GdSdGhj, eMeO MLj GdgGTej HhTYQI,s -- (3Jhaj (B1951s -- (3QMdGJs -- (3GdSYhOjIs -- (3GdMLGRs; (3GdMLs; (3GdMLGL GdeZGQHIs -- (3QMdGJs -- (3GdSYhOjIs -- (3GdMLGRs; (3GdMLGR (B((3GdSYhOjI(B)s -- (3hUa hQMdGJs